Compatibility of Undergraduate Programms to Vietnam National Qualifications Framework: A Case Study at Vietnam National University, Hanoi - Thi Hoai, Tran; Huy, Nghiem Xuan; Thuong, Le Thi (VNU Journal of Science: Education Research; Vol 34 No 2, 2018)
Vietnam National Qualifications Framework was issued under Decision 1982/QĐ-TTg dated 18 October 2016 signed by Prime Minister. Accordingly, programs at tertiary education institutions should be reviewed and adjusted in line with the national qualification framework. Particularly, the correlation between the learning outcomes, program structure, and procedures for building and developing programs in alignment with National Qualifications Framework should be examined and thoroughly resolved, so that higher education institutions have a suitable road map to adjust and update their programs to suit the new context. This paper presents the results of a study on the extent to which National Qualifications Frameworks is met by undergraduate programs. In term of research methodology, this paper uses an analytical perspective on undergraduate programs’ learning outcomes, program development processes, and compatibility and incompatibility of programs’ contents and structure with corresponding competency standards specified in the Vietnam National Qualifications Framework. The research data was collected from the survey and evaluation of undergraduate programs at Vietnam National University, Hanoi.